2023
DOI: 10.3390/ijerph20126136
|View full text |Cite
|
Sign up to set email alerts
|

Dark Personality Traits and Online Behaviors: Portuguese Versions of Cyberstalking, Online Harassment, Flaming and Trolling Scales

Abstract: The main objective of this study is to assess moderation effects of online behaviors between personality traits and addiction to Internet. To this end, four instruments were validated for Portuguese version through confirmatory factor analysis and exploratory factor analysis (Study 1) Multiple regression analysis was applied to examine the personality predictors of specific online behaviors while controlling for gender and age; and moderation effects were assessed (Study 2). Results showed good psychometric pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…Quantitative research has sought to explain individual differences in trolling behaviours through personality approaches and humour-related motivations. Several studies [ 9 , 40 , 41 , 42 ] found psychopathy, as well as Machiavellianism and sadism, most strongly predicted online trolling. For instance, [ 9 ] concluded that online trolling is an “internet manifestation of everyday sadism” and that the internet is essentially a sadist “playground”.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative research has sought to explain individual differences in trolling behaviours through personality approaches and humour-related motivations. Several studies [ 9 , 40 , 41 , 42 ] found psychopathy, as well as Machiavellianism and sadism, most strongly predicted online trolling. For instance, [ 9 ] concluded that online trolling is an “internet manifestation of everyday sadism” and that the internet is essentially a sadist “playground”.…”
Section: Introductionmentioning
confidence: 99%